2006
DOI: 10.1159/000097640
|View full text |Cite
|
Sign up to set email alerts
|

Lp(a) Lipoprotein and Plasminogen Activity in Patients with Different Etiology of Ischemic Stroke

Abstract: Background and Purpose: Lp(a) lipoprotein plays an important part in atherothrombogenesis and is considered an independent risk factor for coronary heart disease. However, its role in cerebrovascular disease remains unclear, in particular because of the heterogeneous nature of strokes. We investigated whether elevated Lp(a) is more frequent in ischemic stroke related to atherothrombosis than in other etiologies of stroke. Because of the close structural homology between Lp(a) and plasminogen, we also studied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 57 publications
3
15
1
2
Order By: Relevance
“…In the NOMASS, the atherosclerotic subtype has been documented in 17% of all cases [25]. Unlike other studies which suggest that elevated Lp(a) is a risk factor for IS caused by large-artery atherosclerosis, we did not find a major difference across infarct subtypes [32]. Our sample size may be inadequate to look for a differential effect across infarct subtypes.…”
Section: Discussioncontrasting
confidence: 68%
“…In the NOMASS, the atherosclerotic subtype has been documented in 17% of all cases [25]. Unlike other studies which suggest that elevated Lp(a) is a risk factor for IS caused by large-artery atherosclerosis, we did not find a major difference across infarct subtypes [32]. Our sample size may be inadequate to look for a differential effect across infarct subtypes.…”
Section: Discussioncontrasting
confidence: 68%
“…The second phenotype, the elevated Lp(a), is caused by a small number of KIVT2 repeats in apo(a) alleles, confirming previous findings which the plasma Lp(a) level is inversely related to the size polymorphisms of apo(a) [21]. An association of elevated Lp(a) with ischemic cerebrovascular disease was demonstrated in several studies [22,23]. Thus, whether the co-occurrence of the two disorders in one family is incidental or whether there is an interaction between both Notch3 and apo(a) genetic defects, is unclear.…”
Section: Discussionsupporting
confidence: 84%
“…Stroke subtypes significantly contributed to heterogeneity assessed by meta-regression; stroke due to large artery atherosclerosis and stroke due to undetermined etiology reported significantly higher ORs (QM ¼ 6.89; p ¼ 0.03; beta ¼ 0.008; se ¼ 0.003). Four studies [47,48,54,56] dichotomized Lp(a) levels at 30 mg/dl (clinical cut-off) or 14 mg/dl, respectively, three studies [27,49,58] compared highest vs. lowest tertile or quartile, respectively, and three studies [45,55,57] reported risk differences for continuous increase in Lp(a), see eTable 6 in the supplement. Four studies reported sex-specific ORs [27,47,48,56].…”
Section: Caseecontrol Studiesmentioning
confidence: 99%